Pengembangan smart edible film packaging berbahan konjac dengan ekstrak bunga rosella dan cangkang telur ayam sebagai bahan aktif: The development of konjac based smart edible film packaging with roselle flower extract and chicken eggshell as active agents - Gregory, Sergio; Setijawaty, Erni; Ignasius Radix A.P. Jati (TEKNOLOGI PANGAN : Media Informasi dan Komunikasi Ilmiah Teknologi Pertanian, 2024)
Edible film is a thin sheet plastic-like biodegradable film that can be used for food packaging material. Edible film can be developed into smart edible film packaging by combining it with smart packaging principles by adding active ingredients. This research aimed to determine the effect of different concentrations of rosella flower extract and chicken eggshell powder on the physicochemical characteristics of smart edible film and its capability to act as smart packaging in a model system. The research design used was a Randomized Block Design with two factors, namely three levels of rosella flower extract concentration and three levels of eggshell powder concentration, all with three replications. The concentration of rosella flower extract used as a treatment in this study was 0 (without rosella flower extract) as a control, 1:15 (w/v of water as solvent), and 1:30 (w/v), while the concentration of eggshell powder used as a treatment in this study was 0 (without eggshell powder) as control; 0.15% (w/v); and 0.30% (w/v). The results showed that the higher the extract concentration added to the formulation, the more the total phenols, anthocyanins, and antioxidant activity would increase. In contrast, the difference in eggshell concentration did not have a significant effect. The tensile strength will increase as the eggshell concentration increases, while the percent elongation will decrease. The water vapor transmission rate (WVTR) decreased with increasing eggshell concentration. There is an increase in color intensity in smart edible packaging used to store steamed chicken meat. Meanwhile, smart edible packaging can prevent damage to steamed chicken meat in terms of color, aroma, and taste.